Indonesian EFL Learners’ Digital Reading Habits - Parlindungan Pardede; Zainal Rafli; Ifan Iskandar (Journal of English Education and Teaching, 2023)
Reading has long been one of the most crucial skills individuals should master to function effectively in society. Due to the revolutionary penetration of information and communication technology (ICT) into almost all aspects of human life, reading has transformed from paper-based to screen-based. Thus, facilitating students to cultivate digital reading should be one of the educational priorities. This study aims at exploring the digital reading habits of students majoring in English as a foreign language (EFL) in Indonesian context. Employing a mixed-methods design, quantitative and qualitative data were collected using an online questionnaire including close-ended and open-ended questions from 79 students of the English Language Education Study Program of Universitas Kristen Indonesia, Jakarta. The results show that a majority of the participants prefer to read in English in digital reading mode due to several reasons. Their most favorable tool for reading is smartphones. Additionally, a majority of them prefer to read at home as far as they have good access to the internet. Finally, based on the analysis of the motivational and de-motivational factors of reading, the participants’ preference towards digital reading has a stronger motivational foundation than print reading.